ACCEPTANCE AND WILLINGNESS TO PAY FOR DENGUE VACCINATION AMONG PARENTS OF CHILDREN AGED 4-15 YEARS IN SOME COMMUNES OF PHU VANG DISTRICT, HUE CITY IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the acceptance rate, willingness to pay, and associated factors related to Dengue vaccination among parents of children aged 4-15 years in several communes of Phu Vang district, Hue city in 2025.Subjects and methods: A cross-sectional study was conducted from May to July 2025 on 430 parents of children aged 4-15 years. Data were collected through face-to-face interviews using a structured questionnaire.Results: The proportion of parents accepting Dengue vaccination for their children was 78.1%, while the willingness-to-pay rate was 80.4%. The most common amount participants were willing to pay ranged from 800,000 to 1,000,000 VND, accounting for 56.7%. The factors of greatest concern when deciding on vaccination were vaccine effectiveness (79.8%), vaccination cost (68.1%), and vaccine safety (64.2%). Acceptance of Dengue vaccination was significantly associated with gender, educational level, household economic status, family history of Dengue fever, knowledge, and Dengue prevention practices (p < 0.05). Willingness to pay was significantly associated with educational level, household economic status, and Dengue prevention practices (p < 0.05).Conclusion: The rates of Dengue vaccine acceptance and willingness to pay were relatively high. Strengthening communication on vaccine effectiveness and safety, together with appropriate financial support policies, is necessary.
Keywords: Dengue fever, Dengue vaccine, vaccine acceptance, willingness to pay.